The Influence of Gender on Puberty-Related Anxiety: A Case Study of Adolescents in Urban School Settings - Tjiptomurti, Peny; Fajriah, Nurul; Kristy, Selvia; Thoyibah Apriliana, Noor; Sovitriana, Rilla (Green Publisher Indonesia, 2026)
Puberty is a critical transitional period in individual development marked by significant biological, psychological, and social changes. This study aims to determine the differences in anxiety levels when facing puberty between male and female adolescents. The method used is a quantitative approach with a comparative design. The research population consisted of students aged 12 to 15 years from SMPN 159 West Jakarta. A sample of 214 students was selected using stratified random sampling. Data were collected through an anxiety scale questionnaire developed by the author based on Spielberger's anxiety theory. One-way ANOVA analysis showed a significant difference in anxiety levels between male and female adolescents. Female adolescents tend to have higher anxiety levels than male adolescents. This study contributes to the understanding of developmental psychology and serves as a basis for psychological interventions in schools.